Eucalyptus obliqua seedling growth in organic vs. mineral soil horizons - Barry, Karen M.; Janos, David P.; Nichols, Scott; Bowman, David M. J. S. (Frontiers in Plant Science, 2015)
Eucalyptus obliqua, the most widespread timber tree in Tasmania, is a pioneer after fire which can eliminate the organic layer of forest soil, exposing the underlying mineral soil. We compared seedling growth, mycorrhiza formation, and mineral nutrient limitation in organic layer versus mineral soil. We grew E. obliqua seedlings separately in pots of organic layer and mineral soil in a glasshouse. Additional treatments of organic soil only, involved fully crossed methyl-bromide fumigation and fertilization. Fertilization comprised chelated iron for 121 days after transplant (DAT) followed by soluble phosphorus. At 357 DAT, whole plant dry weight was three times greater in ambient organic than in mineral soil. In organic soil, fumigation halved ectomycorrhiza abundance and reduced seedling growth at 149 DAT, but by 357 DAT when negative effects of fumigation on seedling growth had disappeared, neither fumigation nor fertilization affected mycorrhiza abundance. Iron fertilization diminished seedling growth, but subsequent phosphorus fertilization improved it. E. obliqua seedlings grow much better in organic layer soil than in mineral soil, although phosphorus remains limiting. The prevalent forestry practice of burning to mineral soil after timber harvest exposes a poor growth medium likely only partially compensated by fire-induced mineral soil alterations.